Comparative Analysis of the Effectiveness of Eco Enzyme from Waste Orange Fruit Peel (Citrus Sp.) and Pineapple (Pineapple Comossus) as an Effort to Sterilize Chicken Coops - Rohana Pakaya; Laksmyn Kadir; Moh. Rivai Nakoe (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Chicken coops are one of the places where pathogenic microorganisms develop that can cause problems for the health of chickens and the surrounding community, so sterilization efforts are necessary. This study aims to compare the effectiveness of eco enzyme liquid from orange and pineapple peel waste in reducing the number of bacteria in chicken coops. A type of pre-experimental research with a one-shot case study design. The samples in this study are two chicken coop samples that were treated each using orange and pineapple eco enzyme liquid . Data collection was carried out before and after treatment with the pour plate method. The data was analyzed using Paired Sample T-Test and Independent Sample T-Test with an error rate of 5%. The results of this study showed that there was a significant decrease in the number of bacterial colonies in cage A (orange) and cage B (pineapple), with significance values of p=0.002 and p=0.001, respectively. However, the results of the comparison test between cages showed no significant difference in the results after treatment (p=0.967). This shows that both eco enzyme liquids are equally effective in reducing the number of bacteria. It is recommended to test the number of bacteria also on other disinfectants to see how much advantages and disadvantages of eco enzymes are compared to commonly used disinfectants.